Proceso de atención de enfermería en gestante de 31 semanas con amenaza de parto prematuro más asma. - Guanulema Capito, Cruscaya Yacila (2021)
Preterm birth is considered to be that which occurs before 37 weeks of gestation (Macias & Espinoza, 2019). According to the World Health Organization, it states that about 15 million children are born prematurely each year. However, in the 184 countries studied, the preterm birth rate ranges between 5% and 18% of newborns (WHO, 2017). It is important to mention that the clinical picture is presented with bleeding and / or colic in the abdomen, contractions with lumbago or pressure in the groin, menorrhagia, thick and mucous discharge with blood from the vaginal canal and rupture of membranes (González, 2016). The diagnosis can be made by abdominal or vaginal ultrasound, pelvic and laboratory exams. Likewise, in the treatment it is important to recommend a lot of bed rest and pelvic rest. On the other hand, the prognosis is a good sign when the bleeding and colic pain resolve (Vega & Butanda, 2020). The following clinical case prepared during my pre-professional stage is based on a 31-week gestation patient who was diagnosed with threatened abortion plus bronchial asthma who came to the emergency area for presenting a clinical picture of colicky pain in the area from the hypogastrium plus vaginal bleeding. Once hospitalized in the gynecology area, a nursing care plan was immediately drawn up to restore the patient's health. By applying and executing the Nursing Care Process that will help us evaluate the results obtained from the Nanda, Noc and Nic and which were put into practice throughout the patient's stay. Achieving a satisfactory recovery and meeting our proposed goals and objectives.